Impact of MRI resolution for Linac-based stereotactic radiosurgery - Huang, Yimei; Liang, Evan; Schaff, Eric M.; Zhao, Bo; Snyder, Karen C.; Chetty, Indrin J.; Shah, Mira M.; Siddiqui, Salim M. (Frontiers in Oncology, 2023)
Objective Magnetic resonance imaging (MRI) is a standard imaging modality in intracranial stereotactic radiosurgery (SRS) for defining target volumes. However, wide disparities in MRI resolution exist, which could directly impact accuracy of target delineation. Here, sequences with various MRI resolution were acquired on phantoms to evaluate the effect on volume definition and dosimetric consequence for cranial SRS. Materials/Methods Four T1-weighted MR sequences with increasing 3D resolution were compared, including two Spin Echo (SE) 2D acquisitions with 5mm and 3mm slice thickness (SE5mm, SE3mm) and two gradient echo 3D acquisitions (TFE, BRAVO). The voxel sizes were 0.4×0.4×5.0, 0.5×0.5×3.0, 0.9×0.9×1.25, and 0.4×0.4×0.5 mm3, respectively. Four phantoms with simulated lesions of different shape and volume (range, 0.53–25.0 cm3) were imaged, resulting in 16 total sets of MRIs. Four radiation oncologists provided contours on individual MR image set. All observer contours were compared with ground truth, defined on CT image according to the absolute dimensions of the target structure, using Dice similarity coefficient (DSC), Hausdorff distance (HD), mean distance-to-agreement (MDA), and the ratio between reconstructed and true volume (Ratiovol). For dosimetric consequence, SRS plans targeting observer volumes were created. The true Paddick conformity index (CIpaddicktrue), calculated with true target volume, was correlated with quality of observer volume. Results All measures of observer contours improved as increasingly higher MRI resolution was provided from SE5mm to BRAVO. The improvement in DSC, HD and MDA was statistically significant (p<0.01). Dosimetrically, CIpaddicktrue strongly correlated with DSC of the planning observer volume (Pearson’s r=0.94, p<0.00001). Conclusions Significant improvement in target definition and reduced inter-observer variation was observed as the MRI resolution improved, which also improved the quality of SRS plans. Results imply that high resolution 3D MR sequences should be used to minimize potential errors in target definition, and multi-slice 2D sequences should be avoided.